Answer:
![\displaystyle f(x)=\left(x+(1)/(2)\right)^2+(3)/(4)](https://img.qammunity.org/2021/formulas/mathematics/college/csdu82mgtfn1ww2xzfmrwy1e08ctzo6grh.png)
Step-by-step explanation:
We are given the function:
.
And we want to turn this into vertex form.
Note that our given function is in the standard form:
![f(x)=ax^2+bx+c](https://img.qammunity.org/2021/formulas/mathematics/middle-school/hj2cyo9lipsf2imfe8tb04vftddbodxbcu.png)
In other words, a = 1, b = 1, and c = 1.
To convert from standard form to vertex form, we can either: (1) complete the square, or (2) find the vertex manually.
In most cases, the second method is more time efficient.
Vertex form is given by:
![f(x)=a(x-h)^2+k](https://img.qammunity.org/2021/formulas/mathematics/high-school/je302k7g40ad9xjfzy7phx2u58uar93mdu.png)
Where a is the leading coefficient and (h, k) is the vertex.
We have already determined that a = 1.
Find the vertex. The x-coordinate of the vertex of a quadratic is given by:
![\displaystyle x=-(b)/(2a)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/n716izs1vyh0mr8nfy9tzs71c9dxpuvygb.png)
Therefore, our point is:
![\displaystyle x=-((1))/(2(1))=-(1)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/1wo8ub08jvrt1oqy1p0pvg01x79z5bpcxa.png)
To find the y-coordinate or k, substitute this value back into the function:
![\displaystyle f\left(-(1)/(2)\right)=\left(-(1)/(2)\right)^2+\left(-(1)/(2)\right)+1=(3)/(4)](https://img.qammunity.org/2021/formulas/mathematics/college/k21b0ram4ttbe3xmkd1imsyn3wrhkq1p3x.png)
Thus, the vertex is (-1/2, 3/4). So, h = -1/2 and k = 3/4.
Hence, the vertex form is:
![\displaystyle f(x)=(1)\left(x-\left(-(1)/(2)\right)\right)^2+\left((3)/(4)\right)](https://img.qammunity.org/2021/formulas/mathematics/college/bawfv0sulbkaqlmtmrsl68ixc0ekfrio51.png)
Simplify:
![\displaystyle f(x)=\left(x+(1)/(2)\right)^2+(3)/(4)](https://img.qammunity.org/2021/formulas/mathematics/college/csdu82mgtfn1ww2xzfmrwy1e08ctzo6grh.png)